Fetal assessment - obstetrical - Gustin, Mazude (2015)
The authors present their experience with the procedure of Fetal Obstetrical Evaluation (FOE) described in Mexico by Dr. Velazco Candamo. They studied 150 pregnant women 30-240 minutes before delivery, and their newborn (Apgar) at 1,5 and 10 minutes of birth. The results obtained with both procedures, FOE and Apgar were similar in neonatal mortality; they conclude the FOE is a reliable procedure that must be complemented with the Apgar evaluation.